To assess role of staffing in nursing productivity: a qualitative research - N Dehghan nayeri; A.A Nazari; M Salsali; F Ahmadi (Tehran University of Medical Sciences, 2006)
Background & Aim: Nurses have the major role at care continuity and health promotion. They frequently affect total productivity in a organization. However, the nurses believe that due to several barriers they have not desire productivity, therefore the health care have been left at level of quality. The aim of this research are assessing nurses;apos view about productivity and role of human resource on it. Methods & Materials: This study has been done based on grounded theory method. Open interviews has been used for gathering of data. Sampling was purposive in beginning study but so that study was proceeding and categories were completed, it changes to theoretic sampling. Constant comparative analysis was method of data analyses. Results: Essential themes emerged from the data in human resource category. These are: systemic calculating number of staff, accurate staff select and use criteria for them, provide adequate staff from various categories in total year;aposs day, accept patient when as coordinate to in charge nurse and well communication. These make necessary groundwork for productivity. Then accidents that emerged from inappropriate quantity and quality of human resource will be decreased. These enhance nursing productivity the biggest group of health care services. Model of Productivity and human resource effects on it's, from nurses;apos view, has concluded of this research. Conclusion: In nurses;apos view that participates in this research, human resource can affect on productivity process and improve it, then it lead to develop quality care- health care vision and goal.